2006
DOI: 10.1111/j.1468-3083.2006.01738.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple neonatal staphylococcal cold abscesses of the large folds

Abstract: Disseminated neonatal staphylococcal infections with a benign evolution are not commonly described in the medical literature. Clinically, cold inflammatory abscesses of the large folds associated with omphalitis may correspond to either transient bacteriemia well controlled in an immunocompetent host or more likely a local contamination process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Dear Editor, Huber et al 1 previously reported three cases of a benign neonatal skin abscess named multiple neonatal staphylococcal cold abscesses of the large skin folds (MNSCAs). Such cases have not been reported since to our knowledge.…”
Section: Multiple Neonatal Staphylococcal Cold Abscesses In Large Skimentioning
confidence: 99%
See 1 more Smart Citation
“…Dear Editor, Huber et al 1 previously reported three cases of a benign neonatal skin abscess named multiple neonatal staphylococcal cold abscesses of the large skin folds (MNSCAs). Such cases have not been reported since to our knowledge.…”
Section: Multiple Neonatal Staphylococcal Cold Abscesses In Large Skimentioning
confidence: 99%
“…Gender, age and Psoriasis area and severity index (PASI) of our study population are comparable to registry data. 1 Adalimumab was administered according to the manufacturer's instructions. 10-15 mg/week methotrexate was usually administered subcutaneously and followed by folic acid substitution.…”
Section: Multiple Neonatal Staphylococcal Cold Abscesses In Large Skimentioning
confidence: 99%
“…1 There are few described cases, most appearing around the tenth day of life as multiple symmetrically distributed nodules in cutaneous folds. 1,2 The pathogenesis of MNSCA remains unknown, although several possible mechanisms can be postulated. The distribution of these nodules in skin overlying regional lymph nodes has led some authors to suggest the primary lesion could be an adenitis.…”
Section: Discussionmentioning
confidence: 99%
“…S. aureus bacterial sepsis, our case is different from previous reports 2) . S. aureus commonly causes superficial or subcutaneous abscesses and is known as an important microorganism causing neonatal sepsis 3) . PICC placement is associated with the known risk of local infection at the PICC insertion site and sepsis caused by S. aureus or S. epidermidis 4) .…”
Section: Discussionmentioning
confidence: 99%